Variabilidade em germoplasma de aveia-preta quanto a caracteres relacionados à aptidão forrageira ou cobertura do solo - Chini, Sílvia Ortiz (2017)
Black oat (Avena strigosa Schreb.) is cultivated for soil coverage and straw production in no-tillage systems, before the summer crops, and as forage production. However, it is not yet part of the breeding program protocol, nor is the registration and protection of genotypes a requirement, evaluations that refer to the genotypes classification as the main aptitude. This makes it difficult for farmers to choose the genotype that best suits their purpose for cultivation. The objective of the presente study was to verify the presence of variability in black oat germplasm with respect to forage value and soil coverage, in order to facilitate breeding programs and genotype classification for aptitude. For this, six cultivars (Agro Coxilha, Agro Planalto, Agro Zebu, Agro Quaraí, Iapar 61 (Ibiporã) and UPFA 21 - Moreninha) and one lineage (Alpha 08626) were tested. The trials were conducted in the field, in 2014 and 2015, in a completely randomized design with three replicates. Agronomic, chemical, morphological, bromatological, and anatomical characters were analyzed by means of variance and multivariate analyses. Genotypes differed on the cycle, biomass productivity and allocation (fresh and dry matter), lignin content (L), cell wall (PC), lignin/nitrogen ratio (L/N) and carbon mineralization (C), crude protein (CP), neutral detergent insoluble fiber (NDF), acid detergent insoluble fiber (ADF), the proportion of mesophyll, epidermis and buliform cells in the leaf blade. With respect to capability for soli coverage there was a negative correlation between C mineralization and L/N ratio and between biomass quality index (BQI) and content of L and PC. Whit respect to forage fitness, leaf/stem ratio was negatively correlated with NDF and ADF and positively with CP in vitro digestibility of dry matter (IVDDM), and total digestible nutrients (TDN). Variability in black oat germplasm was observed for capability for soil coverage and forage fitness, illustrated by the dissimilarity dendrogram obtained by the Ward method, from the Mahalanobis generalized distance. Owing to the lower C mineralization, indicative of lower biomass degradability, the genotypes Agro Zebu, Iapar 61 (Ibiporã) and UPFA 21 - Moreninha are likely to have greater potential for use as soil coverage. The Iapar 61 (Ibiporã) also exhibited indicators of good forage value, such as long cycle, high dry mass production, and attributes related to nutritional value. C mineralization and L/N ratio are important traits for soil coverage, while leaf/stem ratio and NDF content are importante for forage aptitude. It is suggested that the dry matter yield, the cycle, and the biomass allocation, traits traditionally evaluated for genotype classification, should continue to be used for selection, as a way of increasing the distinction between materials.